Fiscal Policy as a Tool for Stabilization in Developing Countries - Kraay, Aart; Serven, Luis (World Bank, Washington, DC, 2013)
The financial crisis of 2007/2008, the subsequent great recession in rich countries and its propagation to developing countries has sparked a renewed interest in the role of fiscal policy as a potential countercyclical tool among policymakers and researchers. This paper reviews the state of empirical evidence on the effectiveness of discretionary countercyclical fiscal policy by placing a particular emphasis on developing countries. On the whole, successful fiscal interventions of this type have been rare in the developing world. This note also briefly reviews contrasting experiences of success and failure in industrial and developing countries. It concludes with several recommendations motivated by past experiences policymakers should consider before adopting any fiscal responses to the current crisis.